Brazilian foreign policy as public policy: elements for analysis and debate - Sorgine, Guilherme Ferreira (2018)
The article aims to deepen the discussion about the analysis of Brazilian foreign policy as a public policy. Without denying certain particularities of foreign policy, one can verify growing similarities between both areas since the inauguration of the Brazilian democratic regime in 1988. This new moment seems to be characterized by a progressive erosion of the proverbial "insulation" of Itamaraty as well as by an approximation of foreign policy to the interests of the Brazilian society.